Prevalência e suscetibilidade bacterianas das infecções do trato urinário em pacientes internados no Hospital Universitário João de Barros Barreto: período de janeiro de 2006 a dezembro de 2007 - SOUZA, Ruy Daniel Ferreira (2023)
Introduction: When there is a need to initiate empirical antibiotics in hospitalized patients with urinary tract infection (UTI), the knowledge of antimicrobial profile of susceptibility in a hospital facilitates the choice of the best antibiotic while it is pending the outcome of the examinations required, such as urine culture and antibiograms. Objective: To know the profile of antimicrobial susceptibility of uropathogens isolated from patients admitted to University Hospital João de Barros Barreto (HUJBB). Methods: This was a individualized, observational and crosssectional study, based on the analysis of urine samples from 2739 patients of which 107 had values > 100.000 CFU/ml of urine culture target of the search. Discussion: The distribution between the sexes was 54.7% women and 45.3% men. The age ranged from 39 to 77 years (65.9%) was the most affected. Escherichia coli bacteria, was the most prevalent (33.64%). Amicacina, Cefazolin, Cefotaxima, Ceftazidima, Ertapenem, Imipenem and Piperacilina/Tazobactan were all 100% sensitive for E. coli. For Pseudomonas aeruginosa, Ciprofloxacina, Ceftazidima and Meropenem showed, respectively, 37.5%, 40% and 69.23% sensitivity. For Klebsiella sp, Amicacina and Imipenem showed good results, with sensitivity equal to 80% and 100% respectively. Fluconazole and Flucitosina were the most sensitive antifungals (100%) for Candida sp. Vancomycin and Penicillin showed excellent sensitivity (100%) for Enterococcus sp. Conclusion: The profile of antimicrobial susceptibility outlined by this study could steer a course of empirical antibiotics in the HUJBB patient when it is needed, reducing the morbimortality of the hospitalized patient with UTI. However, further studies should be made regularly to evaluate the antimicrobial susceptibility profile of the institution, since this is likely to change over time.